Genetic polymorphism of 27 Y-STR loci in Kazakh populations from Central Kazakhstan - Yeldar Ashirbekov; Aigul Zhunussova; Arman Abaildayev; Ayagoz Bukayeva; Zhaxylyk Sabitov; Maxat Zhabagin (Taylor & Francis Group, 2024)
Background The haplotypes from Northern, Southern, Eastern, and Western Kazakhstan, analysed for 27 Y-STR loci, have been contributed to the Y-Chromosome STR Haplotype Reference Database, while the genetic profile of Central Kazakhstan remains inadequately explored.Aim To investigate the genetic diversity of 27 Y-STR loci in the Kazakh populations from Central Kazakhstan.Subjects and methods A total of 112 unrelated Central Kazakh males were genotyped via the Yfiler Plus kit. Data analysis yielded haplotype and allele frequencies, and forensic parameters. Genetic distances were graphically represented by a multidimensional scaling plot, with genetic linkages further elucidated through Nei's distance dendrograms and Median-joining networks.Results A total of 102 haplotypes were detected, of which 96 were unique. The haplotype diversity and discrimination capacity were 0.997 and 0.91, respectively. Central Kazakhstan displays a unique cluster in analyses, underscoring its distinct Y-chromosome diversity compared to other Kazakh regions. The analysis of the Naiman tribe, predominantly residing in Central, Southern and Eastern Kazakhstan, revealed three genetic clusters of distinct haplogroups associated with their clans.Conclusions The identified haplotypes will enhance the existing reference database for Y-chromosomal studies in Kazakhstan, offering a robust tool for future research in population genetics, forensic science and genetic genealogy.